The evaluation of the effectiveness of RESAN vaccine in the prophylaxis and the treatment of endometriosis – an experimental study with an animal model. Part III – Is the histological confirmation of diagnosis necessary? - Szymanowski, Krzysztof; Chmaj-Wierzchowska, Karolina; Niepsuj, Joanna; Yanchanka, Andrey; Florek, Ewa; Barlik, Magdalena; Opala, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Introduction: According to ESHRE guidelines each case of deep and infiltrating endometriosis or endometriosis with endometrial cysts needs to be histopathologically diagnosed. Objective: The aim of this study was to compare preliminary and conclusive diagnoses of endometriosis during experimental study with an animal model. Material and methods: A group of 58 sexually mature female rats was divided into three smaller groups. During the first step of the experiment RESAN vaccine was injected among rats of group I (n=24). Three months later during the 2nd step of examination endometriosis was implanted in groups I and II (n=24). Group III (n=10) was a control group where sham operations were performed. Three months later, endometrial implants were removed and examined histologically. Meanwhile RESAN vaccine was injected as a treatment in group II (step 3). Three months later an excision of the suspected foci was performed with histological examination of the tissue samples (step 4). Cysts and/or adhesions surrounding the implant and/or congestion foci were treated as endometriosis markers. Results: In group I endometriosis was macroscopically diagnosed in 5 cases, but histologically confirmed just in 1 rat. During the 4th step there were no endometriosis markers in group I. During the 2nd step of the experiment endometriosis was suspected in 21 rats and confirmed in 16 cases. Three months later, 12 among 16 rats with endometriosis did not have any signs of that disease in preliminary and conclusive examination. Conclusions: Every macroscopic diagnosis of endometriosis needs to be confirmed with histological examination.